Soldier Tracking and Health Monitoring System - Prof. S.S. Patil; Aishwarya Bajirao Patil; Prof. A. S. Mali (International Journal of Engineering and Management Research, 2023)
In this day and age, fighting is a significant figure any country's security. One of the significant and indispensable jobs is played by the military fighters. There are many worries with respect to the security of troopers. So for their security reason, many instruments are mounted on them to see their wellbeing status as well as their continuous area. Bio-sensor frameworks involve different sorts of little physiological sensors, transmission modules and handling capacities, and can along these lines work with minimal expense wearable unpretentious answers for wellbeing observing. This task provides a capacity to follow the area and screen soundness of the troopers continuously who become derailed and get presence in the war zone. It assists with limiting the time, search and salvage activity endeavours of armed force control unit. This framework empowers to armed force control unit to follow the area and screen soundness of troopers utilizing GPS module and remote body region sensor organizations (WBASNs), for example, temperature sensor, heart beat sensor, and so on. The information coming from sensors and GPS recipient will be communicated to the base station.